Geopolitics In The Triple Border Of Kashmir: Conflicts Between China, Pakistan, And India (2021)
The article addresses, from a historical and geopolitical perspective, the past and current conflicts between China, Pakistan, and India in the triple border of Kashmir; calling attention to its particularity as a geostrategic area. It analyzes the military confrontations and disagreements between China and India; developing an interpretative historical framework that provides elements to understand the relevance of the conflicts in the region. It examines in detail the dispute between India and Pakistan, as part of the British legacy, where ethnic differences are highlighted as a key factor to understand the depth of the problem. It analyzes how the conflicts in Kashmir can be an element that leads the mechanism of the BRICS and the New Silk Road to a possible failure. The increase in conflicts would further involve Russia, the United States, Japan, Australia, Israel, among others.